DECAPITALIZATION OF THE EFFECTIVE RATES TO CALCULATE SIMPLE INTEREST - Avelino Sánchez, Esteban Marino (2014)
The nominal interest rates is normally used to cal-culate simple and compound interest rates (under some assumptions or conditions). In contrast, the effective rate used to calculate simple interest is not usual. However, in Peru used to calculate labor legal interest; then the problem is decapitalize the effecti-ve rate of legal interest, as their accumulated factor, through experiments in Excel, note the properties of the strengthening and establishment, and analyzing the results, which confirmed our a presumption, the possibility to calculate the average cumulative factor built with the effective interest rate of any period to calculate simple interest daily factor, which has been shown in research work in 2013, entitled “financial Mathematics with Applications in Excel “and now embodied in this article.